PERANAN HUKUM INTERNASIONAL TERHADAP KEJAHATAN HUMANITER ATAS KONFLIK RUSIA-UKRAINA - Mulvi Muhammad Ihsan (2023)
The conflict carried out by Russia has openly violated international obligations, in which its actions are clearly a violation of the law and the ideals of the founding of the United Nations. Then this practice must be condemned by all members of the United Nations. Thus, in this study the authors see that the Russian conflict indicated that it was committing war crimes, namely by targeting civilians. Seeing Russia's motives towards Ukraine raises the question of how international law regulates the relationship between war and civilians, and how to resolve the humanitarian issues that occurred in Ukraine. This study aims to discuss how international law regulates crimes that occurred in the Russia-Ukraine conflict against civilians and how efforts to resolve humanitarian crimes through the perspective of international law that occurred from the Russia-Ukraine conflict. The research method in this study is normative juridical.